2018
DOI: 10.1038/s41467-018-03301-0
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive and frequent identification of high avidity neo-epitope specific CD8 + T cells in immunotherapy-naive ovarian cancer

Abstract: Immunotherapy directed against private tumor neo-antigens derived from non-synonymous somatic mutations is a promising strategy of personalized cancer immunotherapy. However, feasibility in low mutational load tumor types remains unknown. Comprehensive and deep analysis of circulating and tumor-infiltrating lymphocytes (TILs) for neo-epitope specific CD8+ T cells has allowed prompt identification of oligoclonal and polyfunctional such cells from most immunotherapy-naive patients with advanced epithelial ovaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
139
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(149 citation statements)
references
References 54 publications
10
139
0
Order By: Relevance
“…First, we were only able to screen autologous TILs that had been long propagated in culture. We have previously reported that TIL ex vivo expansion may lead to depletion of T cell clones that recognize tumor neoantigens 66 . Second, it is possible that the melanoma cells, which had to be expanded considerably in culture for immunopeptidomics analyses, could have altered their HLA peptide repertoire, leading to the identification of noncHLAIp that were originally not present in freshly extracted cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we were only able to screen autologous TILs that had been long propagated in culture. We have previously reported that TIL ex vivo expansion may lead to depletion of T cell clones that recognize tumor neoantigens 66 . Second, it is possible that the melanoma cells, which had to be expanded considerably in culture for immunopeptidomics analyses, could have altered their HLA peptide repertoire, leading to the identification of noncHLAIp that were originally not present in freshly extracted cells.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of circulating antigen-specific T cells in patient 0D5P was performed as previously described 66,93 . CD19+ cells were isolated from cryopreserved PBLs using magnetic beads (Miltenyi) and expanded for 14 days with multimeric-CD40L (Adipogen, Epalinges, Switzerland, 1g/mL) and IL-4 (Miltenyi, 200 IU/mL).…”
Section: Interrogating T-cell Reactivitymentioning
confidence: 99%
“…To address this hypothesis, we performed mRNA sequencing on single- and 20-cell pools of CD8+ T cells isolated from human tumors. As the association between tumor mutational load, CTLs and TLS was uniform across malignancies, we chose ovarian cancer as our model tumor for the sequencing because of its large tumor bulk, high number of infiltrating, neo-antigen recognizing CD8+ cells and documented presence of TLS 16,27 . As TLS are frequently found within the tumor stroma, we also distinguished stromal from intraepithelial CD8+ T cells using the aE integrin subunit (CD103).…”
Section: Resultsmentioning
confidence: 99%
“…Neoantigen-specific T cells can be identified in patients not only with melanoma, but also with epithelial cancers, such as lung cancer [119,120], gastrointestinal cancer [121][122][123], ovarian cancer [124][125][126], breast cancer [127] and pancreatic cancer [128]. Case reports have demonstrated that treatment of the gastrointestinal and breast cancer patients with a T cell population highly enriched in neoepitope-specific T cells caused tumour regression [121,123,127].…”
Section: Selection Of Neoantigen-specific T Cells From the Tumourmentioning
confidence: 99%
“…Rosenberg's group demonstrated that neoantigen-specific T cells could be identified and isolated not only from the tumour, but also from the peripheral blood of melanoma patients [130,131]. Remarkably, neoantigen-specific T cells can be identified also in the peripheral blood of the patients with tumours harbouring relatively low number of mutations such as epithelial cancers [124,132,133]. Detection of rare neoantigen-specific T cells in the peripheral blood can be enhanced by using combinatorial pMHC multimer staining [130].…”
Section: Selection Of Neoantigen-specific T Cells From Peripheral Bloodmentioning
confidence: 99%